Kontradiksi Demokrasi Liberal dan “Akhir Sejarah” Yang Tertunda - Karina, Eva Novi (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
Due to historical developments and the works of theorists such as Francis Fukuyama, predominant political-economic literature has claimed that the combination of a “free market economy” and “liberal democracy built on equal rights” results in the most developed form of human society. With economic and political liberalism, societies of Western Europe and North America “at the vanguard of civilization” considered have reached the endpoint of humankind’s ideological evolution hence Western liberal democracy has been perceived as the final form of human government. However, the current rising wave of right-wing populism along with the exercise of protectionist economic measures in the most developed democratic countries has shown that democracy has begun to malfunction. Depart from this point, this article aims to re-examine the relationship between free market and democracy, and analyses the real inequalities manifested in income and the ownership of the means of production, and the inequalities within capitals, and between capital and wage labor. It concludes that the logic of market mechanisms poses a threat to democracy, while the extension of democracy would inevitably limit the freedom of the market and curb capital accumulation.